The practice and prospect of data factor circulation and security governance in civil aviation field - LIU Yanfang; ZHANG Lei; LI Hanxuan (大数据)
The circulation of data factor is the key to the development of the digital economy, and security first is the principle of building data factor market. This paper focuses on the civil aviation field, and describes the current data resource characteristics and circulation status, as well as the security challenges faced by multi-subject participation. A three-layer model is proposed, which is based on intra-enterprise data governance, intra-industry data circulation and cross-industry data circulation. Taking the data governance practice of Travelsky Technology Limited as an example, this paper introduces data architecture governance, data standard implementation, classification and full life cycle security protection. Finally, data factor circulation and security governance in civil aviation field are prospected.